The improvement on Respiratory Muscle, Trunk Stability, and health status after Abdominal Drawing-in Maneuver in COPD Patients - Winny W; Siti Chandra Widjanantie; Maryastuti M; Nury Nusdwinuringtyas (Indonesian Journal of Physical Medicine & Rehabilitation, 2017)
Background: Chronic Obstructive Pulmonary Disease (COPD) patients experienced respiratory muscledysfunction, postural instability, and decreasing in health status. Abdominal drawing-in maneuver (ADIM) hasbeen studied in many cases of low back pain for lumbar stabilization, moreover this maneuver is also designedto activate the transversus abdominalis (TA) muscle that involved in expiration. But this exercise has not beenconsidered as a respiration exercise in COPD patients. The purpose of this study was to determine whether theapplication of ADIM to COPD patients would affect the strength of respiratory muscle, improve core musclestability, and health status of COPD patients.Methods:All clinically stable COPD patients who visited PMR clinic at Persahabatan General Hospital wererecruited in the study. They received exercise interventions 2 times a week for 4 weeks. ADIM as a mainprogram is using pressure transducer (Chattanooga, Australia). Each exercise was held 10 repetitions, 10 setswith 2 minutes rest. Strength of respiratory muscle measured by peak cough flow (PCF) and peak flow rate(PFR). Core muscle stability measured by functional reach test (FRT) and the health status measured with CATscore. The measurements were done before and immediately after intervention.Results: Subjects were 8 patients with mean age 62 years old, consisted of 7 men and 1 woman, with 1 patienteach with COPD grade A, B, and C, and 5 patients with COPD grade D. There were increasing of PCF (268.75± 59.146 L/min to 285.00 ±59.522 L/min; p=0.061), PFR (251.3±96.3 L/min to 286.3±92 L/min; p=0.028),FRT (20.2±3.8 cm to 22±3.9 cm; p=0.011), and decreasing of CAT score (14 ±8.685 to 11.50 ±8.848; p=0.027)after ADIM.Conclusion: There were an improvement in respiratory muscle, trunk stability, and CAT after ADIM, so themaneuver is effective for COPD management.Keywords: Abdominal drawing-in maneuver (ADIM), Chronic Obstructive Pulmonary Disease (COPD),COPD Assessment Test (CAT), Functional reach test (FRT), Peak cough flow (PCF), Peak flow rate (PFR)